Supplementation with lipid sources alters the ruminal fermentation and duodenal flow of fatty acids in grazing Nellore steers - Carvalho, Isabela Pena Carvalho de [UNESP]; Fiorentini, Giovani [UNESP]; Castagnino, Pablo de Souza [UNESP]; Jesus, Raphael Barbetta de [UNESP]; Messana, Juliana Duarte [UNESP]; Granja-Salcedo, Yury Tatiana [UNESP]; Detmann, Edenio; Padmanabha, Jagadish; McSweeney, Christopher S. [UNESP]; Berchielli, Telma Teresinha [UNESP] (Elsevier, 2017)
Lipid supplementation may adversely affect rumen fermentation, microbial abundance, nutrient utilization and the duodenal flow of fatty acids (FA). In a 5 × 5 Latin square design, 10 Nellore steers with ruminal and duodenal cannulas (292 ± 28 kg BW) were fed one of the five following dietary lipid sources in the concentrate, as follow: (1) no additional fat (WF); (2) palm oil (PO) derived from the Palmaceae plant Orbignya oleifera; (3) linseed oil (LO); (4) protected fat (PF); and (5) whole soybeans (WS). The dry matter intake (DMI) was greater for the animals supplemented with WF than for those supplemented with PO, PF, and WS. The DM digestibility was 11% greater for the animals in the WF group than for those in the PO group. The animals in the PO group had greater duodenal flows of capric (C10:0), lauric (C12:0) and myristic (C14:0) saturated fatty acids (SFA) than did animals in the other groups. The amount of flows of vaccenic acid and total unsaturated acids (UFA) was greater with LO supplementation. The unsaturated fatty acid (UFA) biohydrogenation ratio was greater in the animals supplemented with WS than in those supplemented with PO, LO, and PF. The acetate: propionate ratio was lower in the animals supplemented with PO and LO, at 2.9 and 3.0, respectively. The ruminal flow of particles and rate of fiber degradation were lower with PO supplementation. The proportion of archaea was reduced with the inclusion of PO, LO and PF. PO supplementation resulted in lower total apparent NDF digestibility than did WF, PF, and WS supplementation. Therefore, LO, PF and WS can be used as dietary supplements for grazing cattle without impairing fermentation. The inclusion of PO in the diets of grazing cattle may reduce the number of methanogens and alter fiber utilization.
Keywords: Biohydrogenation; Brachiaria brizantha; Linseed; Microbial population; Palm oil